Understanding Coopetition Dynamics in Manufacturing Value Networks: A System Dynamics Based Causal Loop Diagram (CLD) Modelling Approach - Konyalioglu, Aziz Kemal; Ates, Aylin; Paton, Steve; APAYDIN, TUĞÇE (Springer Science and Business Media Deutschland GmbH, 2024)
The concept of “coopetition” in manufacturing value networks involves firms engaging in both collaboration and competition simultaneously This approach, while aiming to leverage the benefits of both, inherently introduces a paradox concerning value creation and capture. Within a value network, coopetition involves various entities such as suppliers, distributors, subcontractors, and even competitors working together to enhance overall value. Despite a surge in research on coopetition, there remains a disjointed understanding, with limited exploration of its dynamics within manufacturing contexts. To address this gap, our study constructs a system dynamics model using causal loop diagrams (CLD) derived from an in-depth literature review within the manufacturing sector. Our aim is to comprehensively elucidate the factors influencing co-opetitive relationships and dynamics in manufacturing value networks and business ecosystems. Furthermore, existing literature emphasizes the need for a multifaceted perspective on coopetition in manufacturing. Our model, developed through consultation of extensive manufacturing and business literature and CLD application, identifies key factors driving coopetition dynamics in manufacturing and business ecosystem contexts. It represents the first comprehensive content analysis of coopetition dynamics within manufacturing and business ecosystems, serving as a valuable resource for scholars and professionals in the manufacturing and management field. By examining interconnected elements in a causal loop framework specific to manufacturing and business ecosystems, our study reveals how dynamic factors influence co-opetitive outcomes in these ecosystems. We explore various manufacturing-related aspects, such as supply chain dynamics in coopetition, technological innovations, and market dynamics, all impacting co-opetitive interactions. This comprehensive approach fills a literature gap, offering insights into critical factors affecting the co-opetitive process within manufacturing and business value networks. Our study’s methodology, employing causal loop diagrams tailored to the manufacturing domain, stands out in the literature, providing a unique perspective on coopetition dynamics within manufacturing and management contexts. © IFIP International Federation for Information Processing 2024.
43rd IFIP WG 5.7 International Conference on Advances in Production Management Systems, APMS 2024
Keywords: Business; Coopetition; Dynamics; Innovation; Manufacturing